Apoptotic Cell Death and Inhibition of Wnt/β-Catenin Signaling Pathway in Human Colon Cancer Cells by an Active Fraction (HS7) from Taiwanofungus camphoratus. (7th February 2011) - Yeh, Chi-Tai; Yao, Chih-Jung; Yan, Jiann-Long; Chuang, Shuang-En; Lee, Liang-Ming; Chen, Chien-Ming; Yeh, Chuan-Feng; Li, Chi-Han; Lai, Gi-Ming
Abstract : Aberrant activation of Wnt/ β -catenin signaling plays an important role in the development of colon cancer. HS7 is an active fraction extracted from Taiwanofungus camphoratus, which had been widely used as complementary medicine for Taiwan cancer patients in the past decades. In this study, we demonstrated the effects of HS7 on the growth inhibition, apoptosis induction, and Wnt/ β -catenin signaling suppression in human colon cancer cells. HS7 significantly inhibited proliferation of HT29, HCT116, and SW480 colon cancer cells in a dose- and time-dependent manner. The apoptosis induction was evidenced by DNA fragmentation and subG1 accumulation, which was associated with increased Bax/Bcl-2 ratio, activation of caspase-3 and cleavage of PARP. By using Tcf-dependent luciferase activity assay, HS7 was found to inhibit the β -catenin/Tcf transcriptional activities. In addition, HS7 strongly suppressed the binding of Tcf complexes to its DNA-binding site shown in electrophoretic mobility shift assay. This inhibition was further confirmed by the decreased protein levels of Tcf-4 and β -catenin. The β -catenin/Tcf downstream target genes, such as survivin, c-myc, cyclin D1, MMP7, and MT1-MMP involved in apoptosis, invasion, and angiogenesis were also diminished as well. These results indicate that Taiwanofungus camphoratus may provide a benefit as integrative medicine for the treatment of colon cancer.